A comparative study of multimodal digital map interface designs for blind users. (1st January 2015) - Morgan, Neil; Saeed, Mohammed
This research project investigated the issues and opportunities associated with making digital mapping and spatial data more accessible and usable for the blind. Geographical information systems (GIS) enable the storage and manipulation of raster and vector data based upon the spatial relationships of individual features. While GIS predominantly rely on the visual medium for the presentation of data, the ability to store and manipulate spatial relationships offers opportunities to present data using alternative modalities such as speech, sound and haptic feedback. A group of eight blind participants took part in a task driven experiment using two interface designs. The effectiveness of each interface design was assessed through task performance and user experience questionnaires. The results obtained suggest that interface design, data presentation and the use of multiple modalities has the potential to enhance accessibility, usability and support spatial cognition.